Love and Anxiety in the Early Postmodern World of Margaret Atwood’s Dancing Girls - Jennifer MURRAY (E-REA)
This article analyses Margaret Atwood’s 1977 short story collection, Dancing Girls, looking at the evolution of forms of anxiety in the different texts, shifting as they do from individual, or self-directed anxiety, to more community-minded, altruistic forms. The article offers a close reading of some of the individual stories, showing how they contribute to an overall logic related (primarily, but not solely) to male-female relations in the 1960s and 1970s. In spite of the promises of sexual and self liberation of the period, an underlying sense of emptiness, often experienced as impending danger, is perceptible and takes shape within Atwood’s stories as fantasies of violence or victimization, and appears in figures related to gothic imagery and doubleness.